2006
DOI: 10.1097/01.brs.0000247802.91724.7e
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vertebral Wedging Rate Between Supine and Standing Position and its Association With Back Pain: A Prospective Study in Patients With Osteoporotic Vertebral Compression Fractures

Abstract: Changes in vertebral wedging rate between supine and standing position and its association with back pain may give a clue to the pathogenesis of pain from osteoporotic thoracolumbar vertebral compression fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 14 publications
3
33
0
6
Order By: Relevance
“…In agreement with the improvement in WRs, VAS was significantly decreased in three positions for patients in group A and in turning over and standing position for patients in group B. This is consistent with the study by Toyone et al 11 With respect to DWR changes, group B showed significantly lower values compared with group A preoperatively (Po0.001), but there was no significant difference between groups A and B postoperatively and at 1-month follow-up (P ¼ 0.179 and P ¼ 0.558, respectively). These outcomes suggested that symptoms improvement after kyphoplasty was better in patients with significant wedge-shaped changes showing in X-ray imaging in supine and standing positions (group A).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with the improvement in WRs, VAS was significantly decreased in three positions for patients in group A and in turning over and standing position for patients in group B. This is consistent with the study by Toyone et al 11 With respect to DWR changes, group B showed significantly lower values compared with group A preoperatively (Po0.001), but there was no significant difference between groups A and B postoperatively and at 1-month follow-up (P ¼ 0.179 and P ¼ 0.558, respectively). These outcomes suggested that symptoms improvement after kyphoplasty was better in patients with significant wedge-shaped changes showing in X-ray imaging in supine and standing positions (group A).…”
Section: Discussionsupporting
confidence: 92%
“…There were three authors who reported the results of supine lateral and standing lateral radiographs in patients with VBCF. [9][10][11] Among them, Toyone et al 11 suggested that there was a significant correlation between DWR and back pain when standing erect. Results from our study showed that the WRs in both standing and supine positions were significantly reduced by kyphoplasty in both groups A and B (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted above, the factors causing prolonged and intractable back pain in the case of insufficient bone union following OVF are still unknown. Toyone et al reported a significant correlation between back pain and changes in wedging rate from supine to standing positions for OVF of recent onset [31]. In the present study, marked angular instability of the affected vertebral body significantly contributed to severity of back pain.…”
Section: Discussionsupporting
confidence: 52%